2000
DOI: 10.1128/jcm.38.12.4665-4667.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Iodophor and Alcohol Pledgets with the Medi-Flex Blood Culture Prep Kit II for Preventing Contamination of Blood Cultures

Abstract: Iodophor and alcohol pledgets were compared with the Medi-Flex Prep Kit II for skin disinfection before venipuncture. Of 12,367 blood cultures collected, 6,362 were done with conventional pledgets and 6,005 were done with Medi-Flex kits. Contamination occurred in 351 of 6,362 blood cultures (5.5%; range, 3.7 to 8.1%) with conventional pledgets versus 328 of 6,005 (5.5%; range, 3.5 to 7.5%) with Medi-Flex kits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In addition, we conducted audits of phlebotomy technique. As availability of supplies with blood culture collection kits have been associated with decreased contamination rates, 19 we used a continuously stocked phlebotomy cart containing all necessary supplies. Finally, physicians who determined the outcome were blinded to assignment of the skin antiseptics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we conducted audits of phlebotomy technique. As availability of supplies with blood culture collection kits have been associated with decreased contamination rates, 19 we used a continuously stocked phlebotomy cart containing all necessary supplies. Finally, physicians who determined the outcome were blinded to assignment of the skin antiseptics.…”
Section: Discussionmentioning
confidence: 99%
“…Infect Control Hosp Epidemiol 2013;34(1): [15][16][17][18][19][20][21] Blood cultures are a mainstay of diagnostic testing during taminated blood cultures lead to increased hospital length of hospitalization, and identifying pathogens from bacteremic stay (range, 3-3.5 additional days), increased healthcare costs patients directs antimicrobial treatment. Unfortunately, con-(range, $l,000-$8,750), and additional antibiotic use and ditaminated (false-positive) blood cultures are common, with agnostic testing.…”
mentioning
confidence: 99%
“…Previously, Schifman and Pindur 3 noted that the simple substitution of the PREP kit (70% isopropyl/10% acetone scrub and povidone-iodine dispenser; Medi-Flex Hospital Systems, Inc.) for conventional 70% isopropyl pads and 10% povidone-iodine saturated swabs reduced the contamination rate of blood cultures from 4.6% to 2.2% (P = .011, Fisher's exact test). However, Wilson et al 7 found that substitution of a kit containing 2% tincture of iodine and 70% isopropyl alcohol applicators for conventional alcohol and povidone-iodine pledgets did not significantly change the contamination rate. Differences in study design, patient population, and definition of blood culture contamination may account for the discrepancy in the results of these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…812 The mechanism for this more rapid action of the tincture formulation may be that the tincture releas-es free iodine more rapidly, or it may simply be that tincture of iodine is typically suspended in an alcoholic solution and thus dries more rapidly than does aqueous povidoneiodine. 6,7 Not unexpectedly, tincture of iodine was found to be superior to povidone-iodine in reducing the blood culture contamination rate in an emergency department setting. 6 Although there has recently been an increase in the use of tincture of iodine, concerns about the toxicity of the higher concentration of iodine in the tincture preparation prevent its universal acceptance.…”
mentioning
confidence: 96%
“…Potential disinfectants include povidone‐iodine (PI), isopropyl‐alcohol (IPA), iodine tincture (TI), ET and CH. Alcohols appear more efficacious than iodophors in some [8,9] but not all studies [10], and TI appears superior to PI in others [4,5,7]. Only two studies of BCC have used CH; one showed reduced BCC with alcohol plus CH 0.5% v/v compared with PI 10% v/v [11], while the other reported no difference between CH 2% v/v plus IPA 70% v/v and TI 2% v/v plus IPA 70% v/v [12].…”
Section: Status Of Staff Members Who Obtained Blood Culture Specimenmentioning
confidence: 99%